Islam dalam Dinamika Filsafat Hukum, Antara Pemaknaan Nilai Konstruktif dan Destruktif (Lex Jurnalica, 2013)
AbstractIn the Islamic thought, there is a diversity of public understanding of Islam and the verses of Allah Almighty stated in the Quran. Understanding of the various efforts to know and understand it has given rise to various schools of Islamic law that is so rich in Islamic legal thought. Differences on a variety of Islamic thought has now lead to a new understanding of the concept that is the main purpose of the human mind: life and death, or can be said to live in the world and the afterlife. Within the meaning of that destructive group of people with a stream thought see that Islam meant the end of life through death related to the destruction. The emergence of destruction, suicide bombing, and another is a form of destructive understanding of Islam, was born of an effort to deconstruct the Islamic thought that have established. There are two schools faced each other in the value of constructive and destructive interpret of Islamic valuesKeywords: islam, constructive value, destructive valueÂ AbstrakDalam pemahaman secara filosofis, khazanah pemikiran Islam, keragaman dan pemahaman masyarakat Islam atas ayat-ayat Allah Taâ€™ala yang tertuang dalam Quran. Pemahaman yang beragam atas upaya untuk mengetahui dan memahaminya telah melahirkan beragam mazhab hukum Islam yang begitu kaya akan pemikiran hukum Islam. Perbedaan atas beragam pemikiran Islam kini telah menimbulkan sebuah konsep pemahaman yang baru yaitu pemikiran atas tujuan utama manusia: hidup dan mati, atau dapat dikatakan hidup di dunia dan hidup di akhirat. Dalam pemaknaan yang destruktif maka sekelompok orang dengan aliran berfikirnya melihat bahwa Islam dimaknai dengan kehidupan akhir melalui kematian yang berkait dengan kehancuran. Munculnya perusakan, bom bunuh diri, dan lainnya merupakan bentuk dari pemahaman Islam yang destruktif, lahir dari upaya untuk mendekonstruksi pemikiran Islam yang selama ini telah mapan.Kata kunci: islam, nilai konstruktif, nilai destruktif